Optical observations of the 2002cx-like supernova 2014ek and characterizations of SNe Iax. Issue 4 (3rd July 2018) - Li, Linyi; Wang, Xiaofeng; Zhang, Jujia; Arcavi, Iair; Zhang, Tianmeng; Rui, Liming; Hosseinzadeh, Griffin; Howell, D Andrew; McCully, Curtis; Zhang, Kaicheng; Valenti, Stefano; Mo, Jun; et al.
ABSTRACT: We present optical observations of supernova (SN) 2014ek, discovered during the Tsinghua University–National Astronomical Observatories, Chinese Academy of Sciences (NAOC) Transient Survey (TNTS), which shows properties that are consistent with those of SN 2002cx-like events (dubbed as SNe Iax). The photometry indicates that it is underluminous compared with normal SNe Ia, with the absolute V -band peak magnitude being −17.66 ± 0.20 mag. The spectra are characterized by highly ionized Fe iii and intermediate-mass elements (IMEs). The expansion velocity of the ejecta is found to be ∼5000 km s −1 near the maximum light, only half of that measured for normal SNe Ia. The overall spectral evolution is quite similar to that of SN 2002cx and SN 2005hk, while the absorption features of the main IMEs seem to be relatively weaker. The 56 Ni mass synthesized in the explosion is estimated to be about 0.08 M⊙ from the pseudo-bolometric light curve. Based on a large sample of SNe Iax, we examined the relations between peak luminosity, ejecta velocity, decline rate and peak V − R colour, but did not find noticeable correlations between these observables, in particular when a few extreme events like SN 2008ha are excluded from the analysis. For this sample, we also studied the birthplace environments and confirm that they still hold the trend of occurring preferentially in late-type spiral galaxies. Moreover, SNe Iax tend to occur in large star-forming regions of their host galaxies, more similar to SNe Ibc than SNe II, favouring the idea that their progenitors should be associated with very young stellar populations. Nevertheless, the progenitors of SNe Iax may have relatively lower metallicity, as suggested by the evidence that they prefer to explode in outer regions of host galaxies.